Teaching Arabic in State Islamic University - Akmaliyah Akmaliyah; Mohammad Rosyid Ridho (Institut Agama Islam Negeri Palopo, 2020)
AbstractServing as the language of al-Qur'an and everyday Islamic rituals both individually and in public congregation, Arabic is a necessary tool for all Muslims to complete their religious duties; therefore, Arabic subject is offered elsewhere starting from PAUD education to university level in our Muslim majority country. This study is going to discuss a specific aspect regarding the strategy of teaching Arabic in higher education. This specific aspect has already been our concern quite a while; it related to the ‘upgrade’ or the transformation of IAIN institution into UIN in which there are faculties with non-religious subjects and their students whose background are of non-or-minimum earlier religious education. In general, they were educated in public high school and had not enough study in Arabic; they were succinctly not familiar with its linguistic peculiarities. Qualitative in nature and with naturalistic approach, this study unveils the urgency of Arabic language proficiency for these students of non-religious faculties. It reveals as well the need for a shift in teaching strategies at UIN for students in non-religious faculties, in a systematic and proper way so that they may develop interest towards the study of Arabic language